Еколого-ценотичні особливості фрагментованих популяцій Carex strigоsa Huds. (Cyperaceae) в Закарпатті - Данилик, І.М.; Кіш, Р.Я. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
В процессе исследований, проведенных в 2003—2005 гг. на территории пойменных лесов Закарпатской низменности, найден новый для флоры региона вид Carex strigosa Huds. (Cyperaceae Juss.). Публикуются новые данные о его распространении, а также эколого-ценотические особенности его местообитаний, расположенных на восточной границе ареала. Сообщества с участием C. strigosa отнесены к ассоциации Fraxino pannonicae-Ulmetum Soу in Aszуd 1935 corr. Soу 1963 класса Querco—Fagetea Br—Bl. et Vlieg. in Vlieg. 1937 — новой для растительности Украины. Приведены общие результаты изучения популяций, указаны причины их инсуляризации. Установлена реликтовая природа C. strigosa на территории Закарпатья, определен его созологический статус. Сделан вывод о необходимости создания на территории Закарпатской низменности национального природного парка для сохранения уникальных фитоценотических комплексов пойменных лесов. During 2003-2005 investigations on the territory of riverine forests of the Transcarpathian Lowland we discovered Carex strigosa Huds. (Cyperaceae Juss.), a new species for the flora of this region. New data on distribution of this species are provided and eco-cenotic peculiarities of its habitats located in the eastern limit of its range are discussed. Communities with C. strigosa belong to association Fraxino pannonicae-Ulmetum Soó in Aszód 1935 corr. Soó 1963, of Querco-Fagetea Br—Bl. et Vlieg. in Vlieg. 1937 class, which is newly reported for vegetation of Ukraine. General results on characteristics of populations are presented, and causes of their insularization are identified. The relict status of C. strigosa in Transcarpathia is determined, and the sozological (conservational) status of the species is defined. Conclusion is made regarding establishing a national nature park on the territory of riverine forests of the Transcarpathian Lowland, with the purpose of preserving unique vegetation complexes of this region.